The reduction of optimal heat treatment temperature and critical current density enhancement of ex situ processed MgB2 tapes using ball milled filling powder. (January 2018) - Fujii, Hiroki; Iwanade, Akio; Kawada, Satoshi; Kitaguchi, Hitoshi
Highlights: Milled MgB2 powder and controlled process cause J c improvement of ex situ tapes. Optimal heat treatment temperature ( T opt ) decreases to 705–735 °C. Low T opt suppresses the decomposition of MgB2 and growth of crystallites. Abstract: The optimal heat treatment temperature ( T opt ) at which best performance in the critical current density ( J c ) property at 4.2 K is obtained is influenced by the quality or reactivity of the filling powder in ex situ processed MgB2 tapes. Using a controlled fabrication process, the T opt decreases to 705–735 °C, which is lower than previously reported by more than 50 °C. The T opt decrease is effective to suppress both the decomposition of MgB2 and hence the formation of impurities such as MgB4, and the growth of crystallite size which decreases upper critical filed ( H c2 ). These bring about the J c improvement and the J c value at 4.2 K and 10 T reaches 250 A/mm 2 . The milling process also decreases the critical temperature ( T c ) below 30 K. The milled powder is easily contaminated in air and thus, the J c property of the contaminated tapes degrades severely. The contamination can raise the T opt by more than 50 °C, which is probably due to the increased sintering temperature required against contaminated surface layer around the grains acting as a barrier.